Long Chain Fatty Acid Acylated Derivatives of Quercetin-3-O-Glucoside as Antioxidants to Prevent Lipid Oxidation - Sumudu Warnakulasuriya; Ziaullah; H. Rupasinghe (Biomolecules, 2014)
Flavonoids have shown promise as natural plant-based antioxidants for protecting lipids from oxidation. It was hypothesized that their applications in lipophilic food systems can be further enhanced by esterification of flavonoids with fatty acids. Quercetin-3-O-glucoside (Q3G) was esterified individually with six selected long chain fatty acids: stearic acid (STA), oleic acid (OLA), linoleic acid (LNA), α-linolenic acid (ALA), eicosapentaenoic acid (EPA) and decosahexaenoic acid (DHA), using Candida antarctica B lipase as the biocatalyst. The antioxidant activity of esterified flavonoids was evaluated using lipid oxidation model systems of poly-unsaturated fatty acids-rich fish oil and human low density lipoprotein (LDL), in vitro. In the oil-in-water emulsion, Q3G esters exhibited 50% to 100% inhibition in primary oxidation and 30% to 75% inhibition in secondary oxidation. In bulk oil, Q3G esters did not provide considerable protection from lipid oxidation; however, Q3G demonstrated more than 50% inhibition in primary oxidation. EPA, DHA and ALA esters of Q3G showed significantly higher inhibition in Cu2+- and peroxyl radical-induced LDL oxidation in comparison to Q3G.